Validitas Soal-Soal Ujian Nasional Mata Pelajaran Bahasa Indonesia Untuk SMP/ MTs - Muyasaroh, Siti Jamilatul (Universitas Muhammadiyah Surakarta, 2014)
The purpose of this research is to find out the level of the content validity and con struct validity of the questions of the national assessment of Indonesian language subject for junior high school / MTs. The Research method applied in this research was qualitative research method. This research employed the qualitative analysis. To support this qualita tive research, the writer used some tools in the data analysis. They are 1) to figure out the content validity, the writer had matched the test items with the indicators listed in the SKL (Graduation Standard Competency) of the Indonesian Language subject 20102011 aca demic years; 2) For the construct validity, the writer used the evaluation format of multiple choice test items by applying material aspect, construct aspect, and language and culture aspect. After the research was conducted, it can be concluded that the questions of the National Assessment of Indonesian Language Subject for Junior High School / MTs in the 20102012 academic years have high content validity and construct validity. The content validity, the entire indicators in the SKL (Graduation Standard Competency) has been ap plied in the test items. However, the writer found that there are two indicators that are used in four test items. In fact, each indicator should be applied in one test item. The construct validity, by using analysis method of the evaluation format of multiplechoice test items, the writer figured out that 56% 100 % test items are appropriate with the aspects. Meanwhile, the test items which are not deal with the aspects are 16 ? 44%.